Analyzing the Forms of Place Deixis and Discourse Deixis in Laki-Laki Sejati Short Story by Putu Wijaya - Ahmad Taufiq; Viona Erika Jaya (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
Background of the problem: Deixis plays a significant role in shaping meaning, coherence, and connection between characters, plot, and setting in literary texts. Purpose: This study aims to examine how place and discourse deixis affect meaning and narrative coherence in Putu Wijaya’s short story Laki-Laki Sejati, addressing how contextual factors influence the interpretation of language and themes. Method: A descriptive qualitative approach with a pragmatic framework is used to analyze the short story, focusing on primary data from the text and secondary literature related to pragmatics and deixis. Result: The analysis identifies that place deixis consists of both concrete and imaginary types (each occurring four times), while discourse deixis features anaphora (9 occurrences) and cataphora (3 occurrences). These elements enhance the setting, atmosphere, and emotional connection, maintaining narrative coherence. Implication: The findings highlight the importance of deixis in enriching literary analysis, providing insights into how readers engage with characters and themes, and offering valuable applications for studies in pragmatics and narrative techniques in literature.